Gold nanoparticle-loaded multifunctional Ti3C2Tx MXene nanosheets fabricated by in situ reduction to effectively enhance their catalase-like activity for tumor therapy - Guo, Yuhao; Wang, Jinyu; Wu, Xiaomei; Qiao, Qianqian; Liao, Tao; Li, Linwei; Xu, Ziqiang; Zheng, Di-Wei; Kuang, Ying; Yu, Wenqian; Li, Cao (Nano today, 2025)
Designing novel, high-performance nanozymes is essential for developing biocatalytic therapeutics, a promising therapeutic approach. In this work, gold nanoparticles (Au NPs)-loaded Ti3C2Tx MXene nanosheets (Ti3C2Tx-Au) are prepared by in situ reduction and then modified with polyethylene glycol (PEG) to obtain a multifunctional anticancer cascade enzyme system, Ti3C2Tx-Au-PEG (TANP). The photothermal properties of Ti3C2Tx in the near-infrared (NIR) region allow for its use in photothermal therapy (PTT). The complexation of Au NPs with Ti3C2Tx significantly enhances the catalase-like (CAT) activity of TANP, while incubating the glucose oxidase (GOx)- and peroxidase (POD)-like properties of TANP. The strong CAT-like property of TANP allows it to decompose the H2O2 overexpressed in cancer cells into O2, which alleviates hypoxia. It can also be used for glucose catabolism in cancer cells, i.e., GOx-like induced starvation therapy. H2O2, one of the glucose degradation products, can be supplied to TANP to generate O2 and POD-like induced reactive oxygen species (ROS) generation to kill cancer cells. Density functional theory (DFT) calculations provide possible reasons for the enhanced CAT-like activity of Ti3C2Tx-Au. Photothermal can enhance enzyme activity and can also be combined with biocatalytic therapy to achieve good therapeutic effects. [Display omitted] •TANP is prepared by in situ reduction to enhance the CAT-like activity of Ti3C2Tx.•The TANP is a cascade enzyme system with multiple enzyme activities.•PTT enhances the enzymatic activity of TANP resulting in enhanced anticancer effect.•DFT calculations provide possible reasons for the enhanced CAT-like activity.